Facial intramuscular lipoma occurrence following topical cosmetic injection with a mixture of basic fibroblast growth factor: A report of two cases. (4th July 2017) - Liao, Xuan; Zhang, Zhi-Dan; Li, Sheng-Hong; Xiao, Li-Ling; Lu, Jin-Qiang; Xie, Bo; Liu, Hong-Wei
ABSTRACT: Growth factors and cytokines control cell growth, proliferation and differentiation via a network of inter- and intracellular signalling pathways, and are involved in skin self-renewing and wound healing. In recent years, topical and injectable growth factors and cytokines have emerged as an intriguing therapeutic modality that can be harnessed for aesthetic purposes. However, very little data are available on their long-term safety and tolerability. In this report, we describe two cases of patients, who developed intramuscular lipoma of the chin following topical injection with a mixture of basic fibroblast growth factor as the main ingredients for chin augmentation. Biopsies in the two cases were performed at our department, and revealed intramuscular lipoma. Our report indicates that the topical injection of growth factors can lead to tumorigenesis, so health care providers need to be aware of its potential consequences.